2004
DOI: 10.1021/bi049320b
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salt on the Urea-Unfolded Form of Barstar Probed by m Value Measurements

Abstract: To probe for residual structure present in the urea-unfolded form of the small protein barstar, to determine how salt might modulate such structure, and to determine how such structure might affect the stability of the protein, mutant variants that display m values different from that of the wild-type protein have been studied. The mutant proteins were obtained by site-directed mutagenesis at residue positions located on the surface of the folded protein. The m value, which represents the preferential free ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 63 publications
3
20
0
Order By: Relevance
“…46 Moreover, mutational studies by Pradeep and Udgaonkar showed that the replacement of charged residues by neutral amino acid residues changes the energetics of the unfolded state of barstar. 47 Finally, the idea of electrostatic repulsions at high globule densities is supported by our experiments at 1.4 ± 0.2 M urea in the presence of different concentrations of KCl (Fig. 5a-c).…”
Section: Discussionsupporting
confidence: 66%
“…46 Moreover, mutational studies by Pradeep and Udgaonkar showed that the replacement of charged residues by neutral amino acid residues changes the energetics of the unfolded state of barstar. 47 Finally, the idea of electrostatic repulsions at high globule densities is supported by our experiments at 1.4 ± 0.2 M urea in the presence of different concentrations of KCl (Fig. 5a-c).…”
Section: Discussionsupporting
confidence: 66%
“…Several recent studies have shown that charge‐reversal mutations on the surface of proteins can be used to improve electrostatic interactions and increase protein stability (Grimsley et al 1999; Loladze et al 1999; Spector et al 2000; Pradeep and Udgaonkar 2004). In a previous study (Pace et al 2000), we showed that the E74K RNase Sa variant was 1.1 kcal/mol more stable that WT RNase Sa, but the D17K variant was 1.1 kcal/mol less stable than WT RNase Sa.…”
Section: Discussionmentioning
confidence: 99%
“…This distance is significantly smaller than the end-to-end distance of a 25-aa residue-long polypeptide chain in a random coil conformation, which is estimated to be Ϸ37 Å (33). Hence, a decrease in the D-A distance from the dry molten globule state to the U state appears possible only if some residual structure forms in the U state (34)(35)(36). Indeed, the observation that the W4-C97TNB distance, which separates 93 residues in the sequence, is only Ϸ 26Å in the U state suggests that the U state is not a random coil but is compact.…”
Section: Expansion and Contraction Of Intramolecular Distance During mentioning
confidence: 99%